Microbiome analysis reveals dynamic changes of gut microbiota in Guizhou horse and Dutch Warmblood horses - Lan, Yanfang; Li, Yaonan; Wang, Yang (Frontiers in Microbiology, 2025)
In recent years, the importance of gut microbiota in digestive absorption, metabolism, and immunity has garnered increasing attention. China possess abundant horse breed resources, particularly Guizhou horses, which play vital roles in local agriculture, tourism, and transportation. Despite this, there is a lack of comparative studies on the gut microbiota of native Guizhou horses (GZH) and imported Dutch Warmblood horses (WH). To address this gap, fecal samples were collected from both GZH and WH, and 16S rRNA high-throughput sequencing was utilized to analyze the differences in their gut microbiota. The results indicated that compared with GZH, the abundance of the gut bacterial community in WH was significantly higher, whereas the abundance of the gut fungal community was lower. Furthermore, PCoA-based scatter plot analysis demonstrated distinct differences in the structure of gut bacteria and fungi between the two breeds. While both types of horses share similar major bacterial and fungal phyla, significant differences were observed in numerous bacterial and fungal genera. Moreover, functional predictions of gut bacterial communities suggested that WH exhibit a more robust digestive system and enhanced glycan biosynthesis and metabolism capabilities. This is the first report on the comparative analysis of the gut microbiota in GZH and WH. The results emphasize the significant differences in gut microbiota among various horse breeds and offer valuable insights into the composition and structure of gut microbiota in different horse breeds.